Hydrogen/deuterium exchange mass spectrometry reveals distinct mechanisms of viral RNA recognition and activation by RIG-I like receptors - Zheng, Jie (2015)
RIG-I like receptors (RLRs) are the major intracellular immune receptors that recognize viral RNA species, undergo a series of conformational transitions and activate the interferon-mediated antiviral response. However, full-length RLRs resist crystallographic efforts and a molecular description of their activation pathways remains hypothetical. Here we employ Hydrogen/deuterium exchange coupled with mass spectrometry (HDX-MS) to probe the apo states of RLRs and to dissect the molecular details with respect to RNA recognition, ATP hydrolysis and CARDs activation. Our data provide a high-resolution orthogonal view of RLR activation in solutions and offer new evidence for the molecular mechanism of RLR activation.